To CAG or not to CAG? Difficulties in determining submission to the Confidentiality Advisory Group: a commentary. (January 2021) - Ranieri, V; Stynes, H; Kennedy, E
The Confidentiality Advisory Group (CAG) is a specialised body that advises the Health Research Authority (HRA) and the Secretary of State for Health on requests for access to confidential information, in the absence of informed consent from its owners. Its primary role is to oversee the safe use of such information and to counsel the governing bodies mentioned above as to whether such use is appropriate or inappropriate. Researchers who seek access to England or Wales-based confidential data, for medical purposes that are in the interest of the public, are typically required to submit an application to this body. However, it is not always clear to researchers whether requests for access to patient data fit within the remit of the CAG or a Trust's local information governance team. This commentary will, therefore, explore the role of the CAG and reflect on how best to support researchers with this question.